The United States, Russia, and the Gulf Cooperation Council Countries: A New Regional Order in the Middle East?* - Menezes, Gustavo Oliveira Teles De [UNESP]; Nasser, Reginaldo Mattar [UNESP] (Associação Brasileira de Ciência Política, 2024)
The transformations the Middle East has been through since the Arab uprisings of the 2010s, also known as the Arab Spring, have been the subject of intense debate in the literature. In this regard, a relevant issue is the role played by the countries of the Cooperation Council for the Arab States of the Gulf (GCC) and Russia in the face of the United States’ regional influence. Is Russia’s involvement in the Gulf determined exclusively by the logic of great power rivalry, or are there specific dynamics in GCC-Russia relations? Why have GCC states been seeking to diversify their relations with the great powers, a process that includes varying degrees of engagement with Russia, since the context of the Arab uprisings? Taking into account these questions, this article aims to analyze the interactions between Russia, the United States, and the GCC countries since the Arab uprisings of the 2010s. It is argued that, although the intensification of Russian involvement in the Gulf has been enabled by the perception of a US withdrawal from the region, such involvement has an autonomous character based on mutual interests with the GCC countries. Furthermore, the consolidation of the GCC states as a largely autonomous center of power in the Middle East is stressed, a condition that enhances these countries’ ability to develop, with a hedging behavior, relations with both the United States and Russia in a complex regional order.
Keywords: United States; Russia; Middle East; Gulf Cooperation Council; Persian Gulf